COVID-19 and Obesity: Role of Ectopic Visceral and Epicardial Adipose Tissues in Myocardial Injury - Lasbleiz, Adèle; Gaborit, Bénédicte; Soghomonian, Astrid; Bartoli, Axel; Ancel, Patricia; Jacquier, Alexis; Dutour, Anne (Frontiers in Endocrinology, 2021)
In March 2020, the WHO defined COVID-19, caused by SARS-CoV-2, as a global pandemic. Obesity was quickly identified as a risk factor for poor prognosis with an increased risk of intensive care units admission, mechanical ventilation but also cardiovascular events. Obesity is associated with adipose tissue chronic low-grade inflammation and immune dysregulation with hypertrophy and hyperplasia of adipocytes and overexpression of pro-inflammatory cytokines. However, exact mechanisms leading to this loss of chance in these patients must be clarified to implement appropriate therapeutic strategies. The role of white visceral adipose tissue, increased in obese individuals, seems important, acting as a viral reservoir for Sars-Cov-2 via ACE2 receptors. After infecting the host cells, the activation of pro-inflammatory cytokines creates a conducive ground for the “cytokine- storm” and macrophage activation syndrome associated with progression to acute respiratory distress syndrome. In obesity, viral systemic spread, entry and prolonged viral shedding in already inflamed adipose tissue may enhance immune responses and subsequently amplification of cytokine cascade promoting worse outcomes. More precisely, visceral adipose tissue more than subcutaneous fat could predict ICU admission and lower density of epicardial adipose tissue (EAT) could be associated with worse outcome. EAT, an ectopic adipose tissue which surrounds myocardium would be a fuel for COVID-19-induced cardiac injury, myocarditis but also extensive pneumopathy by high expression of inflammatory mediators that could diffuse paracrinally through the vascular wall. The objective of this review is to decipher the mechanisms possibly implicated in unfavorable prognosis in obese patients with COVID-19, especially cardio-vascular events, by developing the deleterious role of excess ectopic adipose tissue, particularly epicardial adipose tissue.